To Study the Impact on the Perception of Banking Customers toward E-Banking (A Case Study of Jk Bank Customers) - Muzzamil Rehman; Dr. Babli Dhiman (HM Journals, 2022)
Modern banking practices, including fractional reserve banking and the issue of banknotes, emerged in the 17th and 18th centuries. Merchants started to store their gold with the goldsmiths of London, who possessed private vaults and charged a fee for that service. The study sought to determine the impact on the perception of J&K bank customers with emerging Modern Banking. The study adopted a Descriptive research design on a sample size of 150 respondents in which 75 respondents were Men and 75 were women respondents which makes our research more sound and concrete, who were selected through Convince Sampling Technique (due to shortage of time because it was a project that requires a lot of time) from a target population of 1500 consisting both men and women, Government employees and self employed and married as well as unmarried which made our research more fruitful. It was concluded that the emerging the Bank was not able to change the perception of the J&K bank customers. The customers of the Bank still consider this Bank as a sound financial Institution for investment, they are also ready to be the customers of this in the future as well, and they also recommend others to avail the facilities from the J&K Bank, which shows the faith and trust on the Bank. They were not impressed by all the modern schemes and policies adopted by the new banks in the State. They are fully satisfied with the services and facilities provided by the Bank. It proved our set hypothesis wrong which was Emerging new banks have changed the perception of J&K bank customers. Finally, it was revealed that the customers of this have the same perception and Image of this Bank as a Universal bank.